Marine Finfish Species Diversification: Current Situation and Prospects in Mediterranean Aquaculture - Abellán E.; Basurco B. (Marine Finfish Species Diversification: Current Situation and Prospects in Mediterranean Aquaculture, 1999)
The Mediterranean aquaculture sector, mainly marine fish farming of sea bass and sea bream, has been notable for its development and growth in the last decade. However, this dramatic increase of production has occurred within a framework of technical constraints and limited markets. Following a brief discussion about technical problems affecting the development of Mediterranean mariculture, we here analyse the species development route. This route is considered within the options offering possibilities for future development, and is seen as a strategy that aims to provide diversity in the market and contributes towards the development of new markets through a product differentiation policy. The route of species diversification, its advantages and constraints, the criteria for selection of species and the necessary steps to develop a new species package are analysed and discussed.